2022
DOI: 10.3390/ijms23105658
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation Using Extracellular Vesicles Encapsulated with MicroRNAs as Novel Drug Delivery Systems

Abstract: Self-tolerance involves protection from self-reactive B and T cells via negative selection during differentiation, programmed cell death, and inhibition of regulatory T cells. The breakdown of immune tolerance triggers various autoimmune diseases, owing to a lack of distinction between self-antigens and non-self-antigens. Exosomes are non-particles that are approximately 50–130 nm in diameter. Extracellular vesicles can be used for in vivo cell-free transmission to enable intracellular delivery of proteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…EVexo is associated with different inflammatory conditions, such as obesity, type-2 diabetes mellitus, kidney diseases, inflammatory bowel disease, several malignancies, and autoimmune diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus and Sjögren's syndrome. Considering their potential to carry different mediators to control inflammatory events (3,5,6). Studies have shown increased EVexo activity in RA, and the origin of EVexo is synovial fibroblasts, synovial fluid, and mesenchymal stem cells (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…EVexo is associated with different inflammatory conditions, such as obesity, type-2 diabetes mellitus, kidney diseases, inflammatory bowel disease, several malignancies, and autoimmune diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus and Sjögren's syndrome. Considering their potential to carry different mediators to control inflammatory events (3,5,6). Studies have shown increased EVexo activity in RA, and the origin of EVexo is synovial fibroblasts, synovial fluid, and mesenchymal stem cells (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown that the level of expression of stimulatory factors crucial for T-cell activation on the exosome surface is lower than that on the DC surface. For example, when comparing direct activation methods, the ability of exosomes is only 5 to 10% of that of DCs [91].…”
Section: Exosomes' Role In Cancer Immune Responsementioning
confidence: 99%
“…Additionally, studies have shown that the level of expression of stimulatory factors crucial for T-cell activation on the exosome surface is lower than that on the DCs surface. For example, when comparing direct activation methods, the ability of exosomes is only 5 to 10% of that of DCs [89].…”
Section: Exosomes' Role In Cancer Immune Responsementioning
confidence: 99%